Entinostat Improves Motor Function and Neuronal Damage Via Downregulating NLRP3 Inflammasome Activation After Spinal Cord Injury - Chen Dai (Frontiers Media S.A., 2021)
Background: Spinal cord injury (SCI), a major public health problem, has no effective treatment. A large number of studies have confirmed that histone deacetylases (HDACs) are involved in the physiologic processes that occur following SCI. We tried to uncover the potential neuroprotective role of entinostat (a class I HDAC inhibitor) in SCI.Methods: We conducted a study on a preclinical mouse model of SCI and OGD-induced neuronal damage to present the role of entinostat by the analysis of motor function, histopathologic damage, local NLRP3 inflammasome activation, and neuronal damage.Results: The results showed that entinostat suppressed HDAC activation (including HDAC1 and HDAC3 expression), improved the grip strength and BMS score, spinal edema, cell death, and local NLRP3 inflammasome activation in the spinal cord following SCI. Furthermore, entinostat significantly increased OGD-inhibited neuronal activity and decreased PI-positive cells, HDAC activation, caspase-1 activation, IL-1β and IL-18 levels, and NLRP3 expression.Conclusion: In summary, we first documented that entinostat improved the motor function, histopathologic damage, and local inflammatory response and NLRP3 inflammasome activation in the spinal cord following SCI and also presented the neuroprotective role of OGD-induced neuronal damage via the NLRP3 inflammasome. Thus, our study has the potential to reveal the interaction between the HDAC and NLRP3 inflammasome in the pathologic process as well as SCI and further promote the clinical indications of HDACi entinostat and clinical treatment for the inflammatory response after SCI.